Mexico : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2007)
This Selected Issues paper analyzes external shocks and business cycle fluctuations in Mexico. The paper examines the relative importance of U.S. demand shocks-and other foreign disturbances-in explaining Mexican output fluctuations. It identifies the dynamic response of Mexico's output to those shocks. The paper investigates which U.S. variables are most relevant to explaining business cycles in Mexico. It analyses potential spillovers and channels of transmission underlying the linkages between the United States and Mexican economies, and focuses on one aspect of the development of the Mexican private mortgage market, the market for mortgage-backed securities.